Faktor-faktor yang Mempengaruhi Belanja Modal pada Kabupaten atau Kota di Provinsi Sumatera Selatan - Zais, Gogor Mustawa (Balance : Jurnal Akuntansi dan Bisnis, 2017)
ABSTRACT The objective of this study was to find out and analyze the impact of regional own revenue (PAD), general allocation fund (DAU) and special allocation fund (DAK) on capital expenditure (BM)  in regencies/towns in South  Sumatera Province  for a period of 2010 to 2014. The data were analyzed by using multiple regression. There were four variables in this research. A dependent variable was capital expenditure (BM) and independent variables were regional own revenue (PAD), general allocation fund (DAU) and special allocation fund (DAK). The results showed that the regional own revenue and special allocation fund variables have positive and significant impact on the capital expenditure. This means that the higher the regional own revenue and special allocation fund, the regencies/towns increased the capital expenditure are also higher. General allocation fund do not have a significant effect on the capital expenditure (BM) in regencies/towns in South Sumatera Province for a period of 2010 to 2014